Growth performance, nutrient intake, and microbial protein synthesis of Indonesian male sheep fed diets containing brewer residue - Suprayogi, Wara Pratitis Sabar; Widyawati, Susi Dwi; Prihatini, Fajar Sari; Patmawati, Novia Rahma; Adi, Vicentius Pritto Pratecha (Revista Acadêmica Ciência Animal, 2021)
Industrial brewing companies produce a high quantity of solid residue rich in nutrient contents that can be utilized as a feed ingredient for fattening sheep. This study aimed to evaluate the optimal proportion between rice bran and brewer residue in Indonesian local sheep. The study was designed as a completely randomized block design with a basal diet consisted of 60% forage and 40% concentrate. In total, 15 male sheep were randomly allocated to receive one of three dietary treatments with five replicates in each (P1 = 70% rice bran + 30% brewer residue; P2 = 50% rice bran + 50% brewer residue; and P3 = 30% rice bran + 70% brewer residue). The parameters observed included nutrient intake, body weight gain, rumen microbial protein synthesis, and NH3 concentration. The results showed that brewer residue did not affect nutrient intakes, average daily gain (ADG), rumen pH, and microbial protein synthesis. However, replacing rice bran with 50% and 70% (inclusion rate of 19% and 29% in the diets, respectively) of brewer residue increased dry matter digestibility and NH3 concentration in the rumen. To conclude, brewer residue can be used up to 29% to replace 70% rice bran used in the diets of Indonesian male local sheep without negatively affected sheep's performance.